Effect of suckler cow vaccination against glycoprotein E (gE)-negative bovine herpesvirus type 1 (BoHV-1) on passive immunity and physiological response to subsequent bovine respiratory disease vaccination of their progeny. (June 2018) - Earley, Bernadette; Tiernan, Katie; Duffy, Catherine; Dunn, Amanda; Waters, Sinead; Morrison, Steven; McGee, Mark
Abstract: The study objectives were: 1) to characterise the development of immunocompetence in beef suckler calves from birth to three months of age, and 2) to trace glycoprotein E (gE)-negative bovine herpesvirus type 1 (BoHV-1) antibodies from dam to calf and subsequent vaccination against pneumonia. Thirty multiparous beef suckler, spring-calving cows, consisting of two genotypes were involved; Limousin × Friesian (LF) and Charolais × Limousin (CL). Cows were immunised against the inactivated antigen strain of BoHV-1 (gE- (IBR marker vaccine) at day − 84 and received a booster at day − 56 relative to the expected calving date (d 0). Calves were immunised at 14 and 42 days of age against PI-3 virus, BRSV and Mannheimia (Pasteurella) haemolytica serotype A1 using a commercial vaccine administered subcutaneously. Additionally, calves were immunised against BoHV-1 at 42 days of age, using 1 dose of a live commercial vaccine administered intranasally. Blood samples were collected from all calves (n = 30) via jugular venipuncture at birth, prior to colostrum feeding (0 h), at 12 h (h), 24 h, 72 h and 168 h after the initial feeding of colostrum, and at d 7, 14, 28, 42, 56 and 84 post birth. The mean ratio of gE negative antibodies circulating in the blood of LF and CL dams pre-partum scored negative to gE ab (S/N ≥ 0.70). Antibody levels of BoHV-1 (wild type ( wt )) peaked at 12 h post-birth in calves and declined thereafter, as the maternal antibodies decayed. There was no difference in BoHV-1 and BRSV antibody levels in calves post vaccination. Highlights: Greater decrease in cow serum IgG concentration in LF cows than CL cows pre-partum. Progeny of LF cows have a greater pre-weaning ADG than the progeny of CL cows. Maternally derived antibodies affects response to vaccination in suckled beef calves.